Combat‐Related Posttraumatic Stress Disorder and Comorbid Major Depression in U.S. Veterans: The Role of Deployment Cycle Adversity and Social Support. Issue 3 (26th March 2020) - Goetter, Elizabeth M.; Hoeppner, Susanne S.; Khan, Amanda J.; Charney, Meredith E.; Wieman, Sarah; Venners, Margaret R.; Avallone, Kimberly M.; Rauch, Sheila A. M.; Simon, Naomi M.
Abstract: Posttraumatic stress disorder (PTSD) and major depressive disorder (MDD) commonly co‐occur in combat veterans, and this comorbidity has been associated with higher levels of distress and more social and economic costs compared to one disorder alone. In a secondary analysis of a multisite randomized controlled trial of a sample of veterans with combat‐related PTSD, we examined the associations among pre‐, peri‐, and postdeployment adversity, social support, and clinician‐diagnosed comorbid MDD. Participants completed the Deployment Risk and Resilience Inventory and the Beck Depression Inventory–II as well as structured clinical interviews for diagnostic status. Among 223 U.S. veterans of the military operations in Iraq and Afghanistan (86.9% male) with primary combat‐related PTSD, 69.5% had current comorbid MDD. After adjustment for sex, a linear regression model indicated that more concerns about family disruptions during deployment, f 2 = 0.065; more harassment during deployment, f 2 = 0.020; and lower ratings of postdeployment social support, f 2 = 0.154, were associated with more severe self‐reported depression symptoms. Interventions that enhance social support as well as societal efforts to foster successful postdeployment reintegration are critical for reducing the mental health burden associated with this highly prevalent comorbidity in veterans with combat‐related PTSD. Resumen: Spanish Abstracts by Asociación Chilena de Estrés Traumático (ACET) El Trastorno de Estrés Postraumático Relacionado con el Combate y Depresión Mayor Comórbida en Veteranos Estadounidenses: El Rol del ciclo de adversidad del despliegue y apoyo social TEPT Y DEPRESIÓN MAYOR EN VETERANOS El trastorno de estrés postraumático (TEPT) y el trastorno depresivo mayor (TDM) suelen coexistir en veteranos de combate, y esta comorbilidad se ha asociado con mayores niveles de angustia y más costos sociales y económicos en comparación con un solo trastorno. En un análisis secundario de un ensayo controlado aleatorio multisitio de una muestra de veteranos con TEPT relacionado con el combate, examinamos las asociaciones entre la adversidad previa, durante y posterior al despliegue, el apoyo social y TDM comórbido diagnosticado por el médico. Los participantes completaron el Inventario de Riesgo de Despliegue y Resiliencia y el Inventario de Depresión de Beck – II, así como entrevistas clínicas estructuradas para el diagnóstico. Entre los 223 veteranos estadounidenses de las operaciones militares en Irak y Afganistán (86.9% hombres) con TEPT primario relacionado con el combate, el 69.5% tenía TDM comórbido concurrente. Después del ajuste por sexo, un modelo de regresión lineal indicó que había más preocupaciones sobre las interrupciones familiares durante el despliegue, f 2 = 0.065; más acoso durante el despliegue, f 2 = 0.020; y calificaciones más bajas de apoyo social posterior al despliegue, f 2 = 0.154, se asociaron con síntomas de depresión autoinformados más graves. Las intervenciones que mejoran el apoyo social, así como los esfuerzos sociales para fomentar la reintegración exitosa después del despliegue son críticos para reducir la carga de salud mental asociada con esta comorbilidad altamente prevalente en veteranos con TEPT relacionado con el combate. 抽象: Traditional and Simplified Chinese Abstracts by the Asian Society for Traumatic Stress Studies (AsianSTSS) 簡體及繁體中文撮要由亞洲創傷心理研究學會翻譯 Combat‐Related Posttraumatic Stress Disorder and Comorbid Major Depression in U.S. Veterans: The Role of Deployment Cycle Adversity and Social Support Traditional Chinese 標題: 美國退役軍人中, 戰鬥相關的創傷後壓力症與重性抑鬱疾患共病:服役週期的逆境和社會支持產生的作用 撮要: 在退役戰鬥軍人中, 創傷後壓力症(PTSD)和重性抑鬱疾患(MDD)同時發生的情況普遍, 而過往研究發現, 這種共病情況相比只患一種疾病, 有較高水平的悲痛及較大的社會和經濟成本。本研究對多地點隨機對照試驗作次級分析, 樣本為有戰鬥相關PTSD的退役軍人。我們檢視樣本服役前、服役時及退役後的逆境、社會支持與臨床確診MDD共病之間的關連。樣本完成了服役風險和恢復力量表、Beck抑鬱症量表II, 及結構性臨床面談以作診斷。樣本為曾參與伊拉克和阿富汗軍事行動的223名美國退役軍人(86.9% 男性), 他們有戰鬥相關的主要PTSD, 69.5%當前有MDD共病。我們對性別作調節後, 線性回歸模型反映, 較關注服役時家庭所受的干擾 (f 2 = 0.065) 、服役時受較多騷擾 (f 2 = 0.020) 及退役後社會支持分數較低 (f 2 = 0.154), 均與抑鬱症症狀自評嚴重度較高有關。有戰鬥相關PTSD的退役軍人中, 這種高度普遍的共病為他們帶來精神負擔。提供增強社會支持的干預治療, 以及社會加強協助軍人退役後重新融入社會, 對於減輕上述人口的精神負擔實為關鍵。 Simplified Chinese 标题: 美国退役军人中, 战斗相关的创伤后压力症与重性抑郁疾患共病:服役周期的逆境和社会支持产生的作用 撮要: 在退役战斗军人中, 创伤后压力症(PTSD)和重性抑郁疾患(MDD)同时发生的情况普遍, 而过往研究发现, 这种共病情况相比只患一种疾病, 有较高水平的悲痛及较大的社会和经济成本。本研究对多地点随机对照试验作次级分析, 样本为有战斗相关PTSD的退役军人。我们检视样本服役前、服役时及退役后的逆境、社会支持与临床确诊MDD共病之间的关连。样本完成了服役风险和恢复力量表、Beck抑郁症量表II, 及结构性临床面谈以作诊断。样本为曾参与伊拉克和阿富汗军事行动的223名美国退役军人(86.9% 男性), 他们有战斗相关的主要PTSD, 69.5%当前有MDD共病。我们对性别作调节后, 线性回归模型反映, 较关注服役时家庭所受的干扰 (f 2 = 0.065) 、服役时受较多骚扰 (f 2 = 0.020) 及退役后社会支持分数较低 (f 2 = 0.154), 均与抑郁症症状自评严重度较高有关。有战斗相关PTSD的退役军人中, 这种高度普遍的共病为他们带来精神负担。提供增强社会支持的干预治疗, 以及社会加强协助军人退役后重新融入社会, 对于减轻上述人口的精神负担实为关键。